The history of blood transfusion in Sub-Saharan Africa - Schneider, William H. (William Howard), 1945- (Perspectives on global health., 2013)
"This first extensive study of the practice of blood transfusion in Africa traces the history of one of the most important therapies in modern medicine from the period of colonial rule to independence and the AIDS epidemic. The introduction of transfusion held great promise for improving health, but like most new medical practices, transfusion needed to be adapted to the needs of sub-Saharan Africa, for which there was no analogous treatment in traditional African medicine. This otherwise beneficent medical procedure also created a "royal road" for microorganisms, and thus played a central part in the emergence of human immune viruses in epidemic form. As with more developed health care systems, blood transfusion practices in sub-Saharan Africa were incapable of detecting the emergence of HIV. As a result, given the wide use of transfusion, it became an important pathway for the initial spread of AIDS. Yet African health officials were not without means to understand and respond to the new danger, thanks to forty years of experience and a framework of appreciating long-standing health risks. The response to this risk, detailed in this book, yields important insight into the history of epidemics and HIV/AIDS. Drawing on research from colonial-era governments, European Red Cross societies, independent African governments, and directly from health officers themselves, this book is the only historical study of the practice of blood transfusion in Africa."--Provided by the publisher